1984
DOI: 10.1111/j.1600-0536.1984.tb00162.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactions in selected patients to 22 fragrance materials

Abstract: 182 patients on the basis of 6 criteria were suspected of suffering from contact sensitization to cosmetics. 77 (42%) gave a positive reaction to one or more of a series of 22 fragrance and flavor raw materials. The hands were most often involved. Cinnamic alcohol, hydroxycitronellal, eugenol, coumarin, and abitol gave the most common positive reactions; less frequent were cinnamic aldehyde, dihydrocoumarin and dimethylcitraconate. Their relevance could not be traced. However, the first 4 substances were the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(33 citation statements)
references
References 37 publications
3
28
1
1
Order By: Relevance
“…Coumarin has occasionally caused positive patch test reactions in patients routinely tested with it, but relevance was not established (86,120 (82).…”
Section: The Fragrance Mix: Very Useful But Not Idealmentioning
confidence: 99%
“…Coumarin has occasionally caused positive patch test reactions in patients routinely tested with it, but relevance was not established (86,120 (82).…”
Section: The Fragrance Mix: Very Useful But Not Idealmentioning
confidence: 99%
“…Coumarin, an ingredient in cosmetics and fragrances, was chosen as the reference chemical, since there is a controversy as to whether coumarin is a contact allergen involved in fragrance allergy. Indeed, coumarin allergy, defined by positive skin patch tests, was observed in up to 6.8% of patients with ACD [9,10,11,12,13]. Moreover, it was shown that coumarin was endowed with irritant properties at the concentration of 8% [13].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, coumarin allergy, defined by positive skin patch tests, was observed in up to 6.8% of patients with ACD [9,10,11,12,13]. Moreover, it was shown that coumarin was endowed with irritant properties at the concentration of 8% [13]. However, in a recent study on the skin reactivity to 14 frequently used chemicals, Frosch et al [14] observed positive patch tests to coumarin in less than 0.3% of the 1,855 ACD patients tested.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of contact sensitization to rubber chemicals is so high in the general population that some 16 of them have been incorporated in the screening series of contact allergens of the International Contact Dermatitis Research Group (Malten et al 1976, Fregert 1974. The frequency with which allergen replacement is demanded by surgeons indicates that contact sensitization to these auxiliary substances is frequent among them, but in addition it can be rather serious if replacement is really impossible in certain cases.…”
mentioning
confidence: 99%